Analisis Recovery Orang Dengan Gangguan Jiwa di Kepulauan Maluku - Suryani; Tasijawa, Fandro Armando; Ratumanan, Tanwey Gerson; Nanuru, Ricardo Freedom; Tuhuteru, Hennie; Makaruku, Alfian Reymon; Nivaan, Goldy Valendria; Tomasoa, Valensya Yeslin; Leutualy, Vanny; Madiuw, Devita; Herwawan, Joan Herly; Hentihu, Emma Khumairah (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2023)
Mental health is still an issue that has not received optimal attention from various parties. It is because there is a large treatment gap with most mental illness disorders not yet detected, there are still many health workers who have not been trained in mental health screening and management programs, and the treatment gap means that many People With Mental Illness (ODGJ) have not treated. This requires an analysis of recovery in the Maluku Islands region to give meaning to the lives of ODGJ even though they experience relapse. The research aims to analyze the recovery of ODGJ in the Maluku Islands region. This research used a cross-sectional approach with 268 respondents spread across five districts/cities of the Maluku Islands. The data analysis used in this research is univariate, bivariate, and multivariate. The research results show that most respondents live in Central Maluku (29.5%). In the bivariate analysis, it was found that the variables gender, religion, marital status, education level, duration of suffering from schizophrenia, living in the same house, drug consumption, and visits to the health center were significantly related to ODGJ recovery (p<0.05). Meanwhile, the variables' age and distance from home to the health center showed a statistically insignificant relationship with ODGJ recovery (p>0.05). Meanwhile,multivariate analysis shows that ODGJ living at home is the strongest predictor (OR=8.295, 95% CI=4.441-10.172) among other variables that influence the recovery of ODGJ in the Maluku Islands. The findings of this research are crucial for developing interventions and policies to promote institutional recovery in the Maluku Islands.